Dua Dunia Dalam Satu Tangan: Lembaga Penerjemahan Pertama Di Hindia Belanda, 1820-1825 - Rusyeni, Rini (Jurnal Penerjemahan, 2016)
In order to win a war, one must know its enemy intimately. It goes in a phrase by Tsun Zu as, “to know your enemy, you must become your enemy.” During the periods of colonization, the Dutch authority in the Netherlands East Indies (now Indonesia) had such ideas through its language policy. The Inlandsche Zaken (The first translation agency in the Netherlands East Indies) was established in order to connect two different words, namely the indigenous societies and colonial government in the Netherlands East Indies. The agency was obliged to study the language and culture in the archipelago. During the first five years of the Inlandsche Zaken (also known as Office of Indigenous Affairs), it had showed remarkable achievements in the unification of local vernaculars and the standardization of Malay. In this paper, I provided several analyses on translation of documents from the archives of this agency kept at the National Archives of the Republic of Indonesia. The purpose is to examine the differences between two similar documents and analyze them on the basis of translation techniques. Each document contains Dutch texts. They are translated into Malay (Dutch texts in these two documents are similar but the Malay translations are different). These documents were created by the Dutch colonial government. My central research question is, How was the language and translation utilized as a tool of subordination towards the indigenous society in the Dutch East Indies? I applied qualitative method by using literature reviews and archival analysis for answering the research question. The research concluded that the Inlandsche Zaken used both the ability of Indigenous languages and cultural knowledge in translating documents. Through this knowledge and ability, The Inlandsche Zaken had played a determinant role in bridging the two worlds in the Netherlands East Indies-namely, the colonial government and the indigenous societies, as well as helped the colonial government in exercising the colonial authority. Keywords: language, colonial authority, culture, translation